Chicoric acid advanced PAQR3 ubiquitination to ameliorate ferroptosis in diabetes nephropathy through the relieving of the interaction between PAQR3 and P110α pathway - Weiwei Zhang; Yong Liu; Jiajun Zhou; Teng Qiu; Haitang Xie; Zhichen Pu (Clinical and Experimental Hypertension)
Purpose This study aimed to examine the impact of CA on DN and elucidate its underlying molecular mechanisms of inflammation.Methods We fed C57BL/6 mice injected with streptozotocin to induce diabetes. In addition, we stimulated NRK-52E cells with 20 mmol/L d-glucose to mimic the diabetic condition.Results Our findings demonstrated that CA effectively reduced blood glucose levels, and improved DN in mice models. Additionally, CA reduced kidney injury and inflammation in both mice models and in vitro models. CA decreased high glucose-induced ferroptosis of NRK-52E cells by inducing GSH/GPX4 axis. Conversely, the ferroptosis activator or the PI3K inhibitor reversed positive effects of CA on DN in both mice and in vitro models. CA suppressed PAQR3 expression in DN models to promote PI3K/AKT activity. The PAQR3 activator reduced the positive effects of CA on DN in vitro models. Moreover, CA directly targeted the PAQR3 protein to enhance the ubiquitination of the PAQR3 protein.Conclusion Overall, our study has uncovered that CA promotes the ubiquitination of PAQR3, leading to the attenuation of ferroptosis in DN. This effect is achieved through the activation of the PI3K/AKT signaling pathways by disrupting the interaction between PAQR3 and the P110α pathway. These findings highlight the potential of CA as a viable therapeutic option for the prevention of DN and other forms of diabetes.